(untitled) (History Journal «Jerónimo Zurita», 2023)
The abbots of Santes Creus, Poblet and Veruela were three ecclesiastical posts that maintained close ties with the Aragonese monarchy, appointed respectively and in successive stages as chaplain to the king, royal almoner, and chaplain to the queen. This close relationship with the monarchy meant that the palaces of the three abbots eventually hosted the kings and their retinue during their visits, and the royal institution itself was involved in their construction, considering them to be its own.